Design of Automatic Bottle Filling Using Raspberry Pi - Hadyan Arifianto; Kusworo Adi; Catur Edi Widodo (Diponegoro University Semarang Indonesia, 2018)
Water consumption is very high, especially in urban areas. This means a good business opportunity for small and medium enterprises. Those enterprises, therefore, require an automatic and affordable device that can fill water into bottles. Raspberry Pi is the center of the control system in designing this automatic bottle filling device. This is because Raspberry Pi comes a with GPIO pin that is used as an input-output controller. GPIO pin receives signal input from switches and sensors that are then processed using Python programming language to drive an actuator and a solenoid valve. Subsequent hardware testing includes tests for water sensor, director motor, alternating motor, and solenoid valve. It is found that the water sensor works at a voltage of 4.18 V and that The DC motor works at 13.92 V. It is also found that the DC motor moves back and forth at 34.77 V when it is moving up, and at -34.77 V, when it is moving down. Meanwhile, the solenoid valve is found to work at 224.9 V. Therefore; it’s very possible to use Raspberry Pi as the center of a control system for an automatic bottle filling device.